High-pressure and stark hole-burning studies of chlorosome antennas from Chlorobium tepidum. - Wu, H M (2000)
Results from high-pressure and Stark hole-burning experiments on isolated chlorosomes from the green sulfur bacterium Chlorobium tepidum are presented, as well as Stark hole-burning data for bacteriochlorophyll c (BChl c) monomers in a poly(vinyl butyral) copolymer film. Large linear pressure shift rates of -0.44 and -0.54 cm(-1)/MPa were observed for the chlorosome BChl c Q(y)-band at 100 K and the lowest Q(y)-exciton level at 12 K, respectively. It is argued that approximately half of the latter shift rate is due to electron exchange coupling between BChl c molecules. The similarity between the above shift rates and those observed for the B875 and B850 BChl a rings of the light-harvesting complexes of purple bacteria is emphasized. For BChl c monomer, fDeltamu++ = 0.35 D, where Deltamu+ is the dipole moment change for the Q(y) transition and f is the local field correction factor. The data establish that Deltamu+ is dominated by the matrix-induced contribution. The change in polarizability (Deltaalpha) for the Q(y) transition of the BChl c monomer is estimated at 19 A(3), which is essentially identical to that of the Chl a monomer. Interestingly, no Stark effects were observed for the lowest exciton level of the chlorosomes (maximum Stark field of 10(5) V/cm). Possible explanations for this are given, and these include consideration of structural models for the chlorosome BChl c aggregates.